2010
DOI: 10.1111/j.1472-4642.2010.00699.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐native salmonids affect amphibian occupancy at multiple spatial scales

Abstract: Aim  The introduction of non‐native species into aquatic environments has been linked with local extinctions and altered distributions of native species. We investigated the effect of non‐native salmonids on the occupancy of two native amphibians, the long‐toed salamander (Ambystoma macrodactylum) and Columbia spotted frog (Rana luteiventris), across three spatial scales: water bodies, small catchments and large catchments.Location  Mountain lakes at ≥ 1500 m elevation were surveyed across the northern Rocky M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 56 publications
(81 reference statements)
3
46
1
2
Order By: Relevance
“…Predatory fish strongly limited the spatial distribution of A. tigrinum, which is consistent with previous studies on fish-amphibian interactions (Hecnar and M'Closkey 1997, Pilliod and Peterson 2001, Pilliod et al 2010. By explicitly focusing on metapopulation processes, our work illustrates how distributional constraints result from high extinction risk and low colonization success at sites with fish predators.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Predatory fish strongly limited the spatial distribution of A. tigrinum, which is consistent with previous studies on fish-amphibian interactions (Hecnar and M'Closkey 1997, Pilliod and Peterson 2001, Pilliod et al 2010. By explicitly focusing on metapopulation processes, our work illustrates how distributional constraints result from high extinction risk and low colonization success at sites with fish predators.…”
Section: Discussionsupporting
confidence: 77%
“…Predatory fish consume the eggs and larvae of many pond-breeding amphibians, and fish negatively influence amphibian reproductive behavior, survival, abundance, and species richness (Sexton et al 1994, Hecnar and M'Closkey 1997, Werner et al 2007, Pope 2008. Although predatory fish can strongly limit the spatial distribution of amphibians (Pilliod et al 2010), the rescue hypothesis may explain the persistence of amphibians in wetlands with fish (Sjö gren Gulve 1994, Pilliod andPeterson 2001). If dispersal moderates the risk of local extinction at sites with fish, conservation efforts may benefit from a spatial perspective on fish-amphibian interactions.…”
Section: Introductionmentioning
confidence: 99%
“…This supports several correlative environmental studies, which suggested that fish habitats are not suitable for many amphibians (Knapp 2005;Orizaola and Braña 2006;Pilliod et al 2010). This confirms the results of our 2002 survey, which showed that paedomorphosis was not expressed in fish ponds (four out of 10 fish ponds were the same in both studies: Denoël et al 2005a).…”
Section: Resistancesupporting
confidence: 74%
“…The negative impact of introduced predatory fish on amphibians has been reported in several studies worldwide [7479] and in the Mediterranean region [36, 80–82]. These impacts occur through direct predation, competition or pathogen transfer [81, 83–87].…”
Section: Discussionmentioning
confidence: 99%